A PSYCHOPATH ANALYSIS ON AMY’S CHARACTER IN GONE GIRL MOVIE - Cicih Nuraeni (Wanastra: Jurnal Bahasa dan Sastra, 2016)
Characters in a film follow the storyline of the film itself. The audience must pay attention to all characters in a film. Those characters play how the story goes. This research aims to explore characters of Amy. Amy is a wife of Nick. Amy is a psychopath in film Gone Girl. The writer will analyze the character of Amy as a psychopath, the causes, and the effect of Amy’s psychopath to her husband. In analyzing the Amy’s psychopath character, the writer refers to McCord (1964) about characteristics of psychopath. They divide psychopath into six categories: Asocial, Uncontrolled Desires, Highly Impulsive, Aggressive, Feels little guilt and a warped capacity for love. Besides analyzing the characteristics of Amy’s psychopath, the writer also covers the causes that makes Amy’s psychopath. In terms of causes, the writer refers to the theory from Page and Coleman (1978). They divide the causes into two: family disruption and economic aspects. The result of the analysis shows that those six characteristics in the theory are found in Amy’s psychopath. While in terms of causes, that family disruption and economic aspects play important role on Amy’s psychopath. The more cause is by family disruption. Related to the effects of Amy’s psychopath to Nick, there are some events that push Nick to follow Amy’s desires.